Iodine-mediated synthesis of benzopyridothiazines via tandem C–H thiolation and amination. Issue 130 (21st December 2015) - Wei, Liang; Xu, Li; Tang, Ri-Yuan
Abstract : Tandem C–H thiolation/amination for benzopyridothiazines. Abstract : The first example of an iodine-mediated tandem C–H thiolation/amination strategy for the synthesis of benzopyridothiazines by the reaction of secondary amines with pyridine disulfides is described.